International Marriage: Life Must Go On! - Yongvanit, Sekson (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
International marriage is marriage between people from two different nations and itis a common phenomenon that occurs daily in todays small-world society. Due tothe changes in this modern world, it is now very easy to be interactive, travel, andexchange information. People from many countries have the opportunity tocommunicate through media such as web pages, email, Face book, or Line. It isalso much easier for people to meet âface to faceâ due to the lower cost of airfares.Sometimes, when there are problems with language, it is possible to hire someoneto help by translating or writing letters to help people connect with each other fromanother country. It is also possible to use a broker company who, for a fee, willcontract and coordinate everything right up until the couple gets marriedThailand is one of the countries where local people enter into marriage withforeigners. Especially, Thai women prefer to marry Westerners, while women fromVietnam or China often choose husbands from Japan, Korea, or Taiwan. Studiesindicate that there are large variances in the age, education, religion, language,culture, life style, and family relationships of the people involved in thesemarriages. The parents of Thai women, who marry a foreigner, although they maynot understand their son in lawâs language, will accept him and be very happy tohave him as a son in law. If they move abroad with their husband, the Thai womenwill visit Thailand every year and many send money back to Thailand regularly.They also plan to return to live in the Thailand when there is an opportunity orwhen their husband retires.Keywords: International Marriage, Germany, Thailand, Way of life